Gaya Kepemimpinan, Beban Kerja dan Kompensasi terhadap Kinerja Karyawan: Leadership Style, Workload, and Compensation and Their Impact on Employee Performance - Arikah Amelia; Faif Yusuf (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to analyze the influence of leadership style, workload, and compensation on the performance of employees of PT. Rempah Aroma Kuningan Jakarta. The research method used is quantitative with a descriptive and causal approach. Data collection was carried out through a questionnaire distributed to 40 employees of the company. Data analysis uses multiple linear regression with the help of SPSS version 26. The results showed that leadership style and workload did not have a significant effect on employee performance, while compensation had a positive and significant effect on employee performance. Simultaneously, these three independent variables have a significant influence on employee performance. These results indicate that adequate compensation can improve employee performance more effectively than other factors. Keywords: Leadership Style, Workload, Compensation, Employee Performance